Role of CD4+ lymphocytes in resistance to mucosal candidiasis. - Cantorna, M T (1991)
The role of CD4+ lymphocytes in resistance of N:NIH(S) III bg/bg nu/+ mice to mucosal candidiasis was evaluated. Alimentary tract colonization with a pure culture of Candida albicans induced a population of lymphocytes in both the Peyer's patches and spleens of bg/bg nu/+ mice, but not bg/bg nu/nu mice, that proliferated and produced interleukin-2 (IL-2) in response to C. albicans antigens. The induction of candida-specific lymphocytes correlated with the clearance of C. albicans from the esophagus and tongue of resistant bg/bg nu/+ mice. Isogenic bg/bg nu/nu mice which do not develop candida-reactive lymphocytes were unable to clear C. albicans from their tongues and esophagi. Treatment of bg/bg nu/+ mice with anti-CD4+ monoclonal antibodies depleted their CD4+ lymphocytes and increased their susceptibility to mucosal candidiasis of the tongue and esophagus. In vivo treatment of bg/bg nu/+ mice with anti-IL-2, anti-gamma interferon (IFN-gamma), or both anti-IL-2 and anti-IFN-gamma monoclonal antibodies did not abrogate their resistance to mucosal candidiasis. Furthermore, treatment of C. albicans-susceptible bg/bg nu/nu mice with IFN-gamma and IL-2 did not protect them from mucosal candidiasis. Thus, CD4+ cells apparently play a critical role in resistance to mucosal candidiasis; however, we were unable to demonstrate a role for IL-2 and IFN-gamma in mediating resistance to mucosal candidiasis.